Cetylpyridinium chloride inhibits human breast tumor cells growth in a no-selective way - García Cuellar, Claudia María; Hernández Delgadillo, René; Solís Soto, Juan Manuel; Meester, Irene; Sánchez Pérez, Yesennia; Nakagoshi Cepeda, Sergio Eduardo; Nakagoshi Cepeda, María Argelia Akemi; Chellam, Shankararaman; Cabral Romero, Claudio (Sage Publishing, 2022)
Objective: Analyze the antitumor capacity of cetylpyridinium chloride (CPC) on human breast tumor cells, and the possible action mechanism. Material and methods: The human breast tumor cells MCF-7 and no-tumor breast cells MCF-10A were exposed to CPC under various condition (concentration and duration). Cell viability was measured with MTT assay, the LIVE/DEAD assay, and fluorescence microscopy. Membrane permeability after CPC exposure was evaluated by Calcein AM assay, mitochondrial morphology with a MitoView staining, and genotoxicity with the comet assay and fluorescence microscopy. Results: CPC was cytotoxic to both MCF-7 and MCF-10A as of a 24-h exposure to 0.1 µM. Cytotoxicity was dose-dependent and reached 91% for MCF-7 and 78% for MCF-10A after a 24-h exposure to 100 µM CPC, which outperformed the positive control doxorubicin in effectiveness and selectivity. The LD50 of CPC on was 6 µM for MCF-7 and 8 µM for MCF-10A, yielding a selectivity index of 1.41. A time response analysis revealed 64% dead cells after only 5 min of exposure to 100 µM CPC. With respect to the action mechanisms, the comet assay did not reveal genome fragmentation. On the other hand, membrane damage was dose-dependent and may also affect mitochondrial morphology. Conclusion: Cetylpyridinium chloride inhibits MCF-7 cell growing in a non-selective way as of 5 min of exposure. The action mechanism of CPC on tumor cells involves cell membrane damage without change neither mitochondrial morphology nor genotoxicity.